(untitled) (International Journal of Engineering and Computer Science, 2023)
This paper focus on technologies that could help preventing expensive unexpected failures of Equipments which are backbone for the plant operations in energy industry especially in Oil & Gas which is a vast field with numerous equipments and engineering systems that require constant monitoring and maintenance. With innovative technologies available today, energy industry is rapidly growing and have no alternate other than embracing the digital technologies to reinforce their operation and protect their valuable assess.